Aktivitas Antibiotik Isolat Bakteri Kp13 dan Analisa Kebocoran Sel Bakteri Escherichia coli - Alfian Syarifuddin; Nanik Sulistyani; Kintoko Kintoko (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
A bacterium is one of microorganisms that can produce secondary metabolite, such as antibiotic. KP13 isolate is a bacterium isolated from Melaleucaleuca dendron L rhizosphere. The aim of this study is to know the eff ect of the most active fraction antibacterium of KP13 isolate toward Escherichia coli bacterium and the ability to caused cell leakage. Extraction of antibiotic was conducted by ethyl acetate. Extract is fractioned with a n-heksan-etilacetate solvent gradient another uses a solvent methanol. Each fraction is done by KLT and grouped based on RF value. A fraction group is compare by inhibition eff ectiveness. Then, the Minimum Inhibitory Concentration (MIC) from the most active group is tested. Cell leakage analysis was performed using UV spectrophotometry to detect the release of nucleic acid and protein. Atomic Absorption Spectrophotometry (AAS) was used to detect ion release of K+ and Ca2+ from. cell of bacteria. The results showed that the most active fraction against Escherichia coli was the fraction number 1 with MIC value of 5% and inhibition zone of 7.33±0.58 mm.